Pengaruh Pemberian Pupuk Organik Cair (POC) dari Kulit Durian (Durio zibethinus Murr.) terhadap Pertumbuhan Tanaman Sawi Hijau (Brassica juncea L.) - Yolanda Sulastri Simanjuntak; Fauziyah Harahap; Nusyirwan Nusyirwan (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to determine the effect of Liquid Organic Fertilizer (POC) from durian peel (Durio zibethinus Murr.) on the growth of mustard greens (Brassica juncea L.). This study was conducted at the Greenhouse, Medan State University using a non-factorial Completely Randomized Design (CRD) consisting of four treatments with six replications, resulting in 24 experimental units. The parameters observed included plant height, number of leaves, root length, fresh weight, and dry weight of the plant. Based on the results of the study, it was found that the levels of nutrients contained in the liquid organic fertilizer from durian peel waste were 0.93% C-Organic, 0.36% Total Nitrogen, 0.21% P2O5, 0.05% K2O, and 0.02% Total Ca. The application of liquid organic fertilizer from durian peel waste had a significant effect (p <0.05) on all growth and production parameters of mustard greens (Brassica juncea L.). Based on the results of the Duncan's Multiple Range Test (DMRT), the most optimal treatment for mustard greens growth was a concentration of 300 ml of Organic Fertilizer (POC) and 1,000 ml of water. This indicates that the nutrient absorption effectiveness of durian peel POC is sufficient to support maximum vegetative plant growth.